Engineering Technology for Increasing Soybean Production and to Control Damping-off Disease Using Biological Fertilization Mixture - Ika Rochdjatun Sastrahidayat (Research Journal of Life Science, 2014)
Fall seedling diseases (damping-off) caused by Sclerotium rolfsii is one factor in low productivity of soybean in Indonesia, which may cause loss results achieved 30-75% depending on the level of attacks. Given the character of soil borne diseases (soil borne), then all control efforts through many obstacles, either because the pathogen can survive for decades in the form resistant propagules (Sclerotium) although there is no host for the development.This study aimed to find ways to control the disease by utilizing the potential of natural biological materials and find ways to get control for effective results. For this purpose the various steps of research has been conducted both in laboratory and greenhouse using experimental research design (completely randomized design) and F test to see the difference. The results show that in the first year of research proven to provide results tuba root extract is effective in controlling pathogens. Streptomyces isolates proved to be antagonistic to Sclerotium rolfsii, and when combined with mycorrhizae (AM) will be able to increase its effectiveness. Introduction of inoculum will likely increase their effectiveness when mixed directly into cropping land that can be done as a biological fertilizer just before planting. There is a tendency that the combination treatment between biopesticide will help the effectiveness of its control, though not necessarily affect the production, so the increase in soybean production is due to the protection of soybean from the dead early in the seedling that can suppress up to 50 percent compared with the control.